INDUSTRIAL PARKS AS A MECHANISM OF ATTRACTING INVESTMENTS IN THE REGIONS OF RUSSIA (International Journal of Innovative Technologies in Economy, 2018)
This article is devoted to a research of experience of creation of industrial parks in Russian regions. Conclusions are drawn: 1. To attract foreign investors to the regions of Russia, a unified development program and a single approach that is understandable to foreign investors is needed. This approach was the standard technology of creating industrial parks. 2. We need to understand that we need those investments that will bring high technologies to Russia. Just the opening of foreign productions, which will crush the domestic market with their goods, is not effective for the development of the country and its regions. 3. It is recommended to create an effective mechanism for regulating the investment process in the regions of Russia, ensuring the maximum positive return on investment for the process of their social and economic development and protection of public interests.